Association of physical and technical activities with partial match status in a soccer professional team - Moalla, W.; Fessi, M. S.; Makni, E.; Dellal, A.; Filetti, C.; Di Salvo, V.; Chamari, K. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to examine the association between physical and technical activities and partial match status (winning, drawing, or losing) in a professional soccer team over 2 seasons. Physical and technical activities of 52 official matches were collected and analyzed at each 15-minute interval, for each half (45 minutes), and full match (90 minutes) using a multiple-camera computerized tracking system. The results indicated that according to full match outcome: winning status was characterized by players covering more total distance (p = 0.05) and low-intensity running (<14.4 km/h) (p = 0.05), whereas, losing status induced more sprinting (=25.2 km/h) (p < 0.01) and high-intensity running (=19.8 km/h) (p = 0.05). However, according to partial match status (i.e., 15 minutes and half time), players covered more distance for all running intensities while winning (p < 0.01). Technical match performance scores were not influenced by match status. In conclusion, the present study showed that the physical activities including high-intensity running and total distance covered were related to the match status, whereas technical activities were not. The overall outcome shows that higher physical activity was associated with winning partial match periods. This approach highlights the importance of physical fitness in soccer and may help coaches to better modulate players' roles and team tactical organization throughout the match.